2017
DOI: 10.1016/s1473-3099(17)30323-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of avian influenza A H7N9 virus in human beings across five epidemics in mainland China, 2013–17: an epidemiological study of laboratory-confirmed case series

Abstract: SUMMARY Background Avian influenza A(H7N9) virus has caused human infections in China since 2013, and a large epidemic in 2016–17 has prompted concerns of whether the epidemiology has changed to suggest an increasing pandemic threat. Our study aimed to describe the epidemiological characteristics, clinical severity, and time-to-event distributions of A(H7N9) case-patients in the 2016–17 epidemic wave compared with previous waves. Methods We obtained information about all laboratory-confirmed human cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
232
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 259 publications
(255 citation statements)
references
References 26 publications
9
232
3
Order By: Relevance
“…Our study also demonstrated that the demographic characteristics and exposure patterns of H7N9 cases had no significant changes during the most recent waves. However, there was a wide geographic distribution of cases as well as new occurring districts/counties in the fifth epidemic comparing with the third and fourth waves, which was also consistent to the above‐mentioned studies 9, 10, 18. Moreover, despite the wide geographic coverage of cases in the fifth wave, the larger proportion of them actually occurred in the non‐LPMs closure areas.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study also demonstrated that the demographic characteristics and exposure patterns of H7N9 cases had no significant changes during the most recent waves. However, there was a wide geographic distribution of cases as well as new occurring districts/counties in the fifth epidemic comparing with the third and fourth waves, which was also consistent to the above‐mentioned studies 9, 10, 18. Moreover, despite the wide geographic coverage of cases in the fifth wave, the larger proportion of them actually occurred in the non‐LPMs closure areas.…”
Section: Discussionsupporting
confidence: 86%
“…The national study showed that the main epidemiological characteristics remained unchanged 9, 10. Another study conducted in Jiangsu province, the most impacted province in China in the fifth wave, also reached similar conclusions 18.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Since the initial outbreak, waves of A(H7N9) virus infections in humans have reappeared each winter season, resulting in numerous human infections and deaths 25. We generated and characterized several mAbs recognizing different epitopes on the H7 HA and evaluated these mAbs, as well as H7 mAbs (mAbs 62 and 98) that were developed several years prior to the A(H7N9) outbreak in China, for potency determination of A(H7N9) vaccines using two assay formats.…”
Section: Discussionmentioning
confidence: 99%